2 D MXene‐based Energy Storage Materials: Interfacial Structure Design and Functionalization. Issue 6 (8th November 2019) - Fang, Ruyi; Lu, Chengwei; Chen, Anqi; Wang, Kun; Huang, Hui; Gan, Yongping; Liang, Chu; Zhang, Jun; Tao, Xinyong; Xia, Yang; Zhang, Wenkui
Abstract: Transition metal carbides and/or nitrides (MXenes), a burgeoning group of 2 D layer‐structure compounds, have multiple merits, such as high electrical conductivity, tunable layer structure, small band gap, and functionalized redox‐active surface, and are receiving significant attention as one of the most promising class of energy storage materials. The synthesis methods, structural configuration, and surface chemistry of MXenes directly influence their performance. This Minireview focuses on interfacial structure design and functionalization of MXenes and MXene‐based energy storage materials and the effect of structural configuration and surface chemistry on their electrochemical performance. Additionally, the structure–property relationships between interfacial structure, functional group, interlayer spacing, and the corresponding energy storage performance are summarized in detail. Finally, light is shed on the perspectives for the future research on advanced MXene‐based energy storage materials including scientific and technical challenges. Abstract : Tuning MXenes : Recent synthesis methods of MXene‐based materials, as well as the structure–property relationships arising from interfacial structure, functional groups, interlayer spacing, and electrochemical performance, are thoroughly discussed in this Minireview. Future prospects and development trends relating to the rational design and controllable synthesis of MXenes for various energy storage applications are briefly outlined.